2023
DOI: 10.3390/app13085097
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Anti-Explosion Performance of the Different Types of Structures in Rock under the Condition of Plane Charge Explosion Loading

Abstract: In this paper, the straight-wall-arch structure in the rock medium is taken as the research object, and the high-pressure plane charge loading test technology is adopted to study the anti-explosion performance of different types of structures under the explosion loading. Three types of structures, which are individually built with the high-performance reinforced concrete, the C30 reinforced concrete, and the C30 reinforced concrete with a foam concrete backfill layer as well, are tested, and the dynamic respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…When an engineered structure is subjected to an unexpected load, such as an explosion load or an impact load, resulting in the failure of its components, the failure time of the structural components is generally very short [28]. It is shown that the failure time of the load-bearing component at the bottom floor has a significant impact on the dynamic response of the remaining structure.…”
Section: Failure Time Of the Columnmentioning
confidence: 99%
“…When an engineered structure is subjected to an unexpected load, such as an explosion load or an impact load, resulting in the failure of its components, the failure time of the structural components is generally very short [28]. It is shown that the failure time of the load-bearing component at the bottom floor has a significant impact on the dynamic response of the remaining structure.…”
Section: Failure Time Of the Columnmentioning
confidence: 99%
“…When an engineer structure is subjected to an unexpected load, such as an explosion load, or an impact load, resulting in the failure of its components, the failure time of the structural components is generally very short [23]. It is shown that the failure time of the load-bearing component at the bottom floor has a significant impact on the dynamic response of the remaining structure.…”
Section: Failure Time Of the Columnmentioning
confidence: 99%
“…The research results have also been widely applied to field engineering. Some scholars have actively explored the blast resistance of anchoring and shotcrete-supported caverns [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]: Singh [1] studied the problem of blasting damage to underground mine caverns and discussed the main factors leading to cracks and peeling of the surrounding rock of caverns and proposed that the vibration amplitude of the surrounding rock caused by blasting is an important reference. By using UDEC software, Hagedorn [2] studied and analyzed the stability of anchor-spray-supported caverns after two successive impulsive loads.…”
Section: Introductionmentioning
confidence: 99%
“…By using UDEC software, Hagedorn [2] studied and analyzed the stability of anchor-spray-supported caverns after two successive impulsive loads. Nan et al [3] used the high-pressure plane charge loading test technique to study the blast resistance of different types of structures in the rock medium, focusing on the direct wall arch structure. Three types of structures were tested: high-performance reinforced concrete, C30 reinforced concrete, and C30 reinforced concrete with foam concrete backfill.…”
Section: Introductionmentioning
confidence: 99%